Becoming black : black African nurses racial experiences in Finland, pre-migration to post-migration - Yabal, Judith (2020)
The aim of this study is to contribute to the process of Nursing student mentorship, to better assist Black African nurses/students alongside other minority nurses, in their integration into the Finnish nursing workplace/work practice environment. In this exploratory study, through interviewing, the subjective views and opinions on race of Black African nurses and nursing student participants are explored. This study seeks to better understand participants' views of their race and its relevance in their everyday interactions within the Finnish environment. Subjective views on race from participants are collected from a pre-migration to post migration period. The findings of this study highlight ways participants (n = 6) have experienced negative changes in their transition from racial majorities to racial minorities; in terms of negative self image, poor integration, poor professional advancement opportunities, racism and negative stereotyping of Black Africans in Finland.